Upholding United Nations Global Legitimacy in Human Rights Protection and Humanitarian Assistance within the European Union: A Legal Overview of the EU-UN Natural Partnership - Nives Mazur Kumrić (Poredbeno Pomorsko Pravo)
Promoting respect for human rights and providing humanitarian assistance exemplify one of the core shared values and objectives of the EU-UN agenda, deeply rooted in the premise that universal values of peace, equal rights, freedom, and human dignity may be effectively defended through efficient multilateralism only. The paper aims to offer a deep analysis of the legal framework underpinning the EU-UN partnership and to underscore the critical intersections of the EU and UN systems of addressing human rights protection and unimpeded access to humanitarian assistance. The research builds on Article 21 of the Treaty on European Union, which sets the basis for the EU´s action on the international scene in line with the principles of the Charter of the UN and international law, including the promotion of multilateral solutions to common issues in the area of human rights and humanitarian assistance. Particular emphasis is put on the EU priorities for the UN, adopted annually by the Council´s conclusions guiding the EU´s yearly work adapted to the UN´s agenda and global affairs. Alongside the examination of the current positive law and corresponding scholarly literature, the paper also provides insight into the best practices of the EU-UN natural partnership on the ground, such as the early recovery of war-affected communities in Ukraine through the UN Development Programme (UNDP). Thus, the paper combines doctrinal legal research with the socio-legal approach in outlining the specificities of the EU-UN multi-layered cooperation with respect to human rights protection and humanitarian assistance.